DISRUPTION ON REGIONAL ROAD MANAGEMENT - Dedy Gunawan; Slamet Muljono (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2018)
Abstract This paper describes the disruption of Directorate General of Highway, Ministry of Public Works and Housing, in improving the good governance and financing systems for the execution of regional road. Together with Australia Government through Indonesia Infrastructure Initiative Program, Directorate General of Highway made a grant program called Provincial Road Improvements and Maintenance in the Province of Nusa Tenggara Barat. This program is delivered through pre-financing by local budget and reimbursement grant scheme maximum of 40% by the Central Government with incentives around 10% from total program. Provincial Road Improvements and Maintenance applies good governance and open government principles by involving the road authorities, service provider, and road users through Road Transport and Traffic Forum.The Provincial Road Improvements and Maintenance program successfully improved the stability and service of roads in the Province of Nusa Tenggara Barat with the optimum budget. The program also encourages women participation in order to improve gender equality. As a result, Bappenas with the Ministry of Public Works and Housing and Ministry of Finance plan to replicate this program for the broader coverage in 2018. Keywords: regional road, road stability, road service, road maintenance, road improvement  Abstrak Makalah ini menjelaskan persoalan yang dihadapi oleh Direktorat Jenderal Bina Marga, Kementerian Pekerjaan Umum dan Perumahan Rakyat, dalam memperbaiki tata pemerintahan dan sistem pembiayaan yang baik untuk menangani jalan daerah. Bersama Pemerintah Australia, melalui Program Inisiatif Infrastruktur Indonesia, Direktorat Jenderal Bina Marga membuat program hibah yang disebut Provincial Road Improvements and Maintenance di Provinsi Nusa Tenggara Barat. Program ini disampaikan melalui pre-financing dengan skema kompensasi anggaran daerah dan penggantian maksimum sebesar 40% oleh Pemerintah Pusat dengan insentif sekitar 10% dari total program. Provincial Road Improvements and Maintenance menerapkan tata pemerintahan yang baik dan prinsip-prinsip pemerintahan yang terbuka dengan melibatkan pihak penyelenggara jalan, penyedia jasa, dan pengguna jalan melalui Forum Lalulintas Jalan. Program Provincial Road Improvements and Maintenance berhasil memperbaiki kemantapan dan pelayanan jalan di Provinsi Nusa Tenggara Barat dengan dana yang optimal. Program ini juga mendorong partisipasi perempuan dalam rangka meningkatkan kesetaraan jender. Hasilnya adalah bahwa Bappenas bersama Kementerian Pekerjaan Umum dan Perumahan Rakyat dan Kementerian Keuangan berencana untuk mereplikasi program ini untuk cakupan yang lebih luas pada tahun 2018. Kata-kata kunci: jalan daerah, kemantapan jalan, pelayanan jalan, pemeliharaan jalan, peningkatan jalan